Bản tổng hợp, giải trình, tiếp thu ý kiến các bộ, ngành đối với dự thảo luật các tổ chức tín dụng - Quốc hội Khoá XV (2023)
Toàn văn Bản tổng hợp, giải trình, tiếp thu ý kiến các bộ, ngành đối với dự thảo luật các tổ chức tín dụng.